Improved O-serotyping method for Serratia marcescens. - Gaston, M A (1989)
In a previous study, we found that some O serotypes of Serratia marcescens, as defined by agglutination tests, were not based on lipopolysaccharide (LPS) O antigens. We developed a dot enzyme immunoassay with a high degree of LPS specificity and tested 104 distinct clinical strains. Only 7 of the 24 existing O antigens were found in more than one strain: O12/O14 (30.8% of strains examined), O21 (12.5%), O8 (8.7%), O6/O7 (5.8%), O4 (3.8%), O18 (2.9%), and O9 (2.9%). Two new antigens, S1254 (13.5%) and S3255 (3.8%), were also found. Agglutination tests with O antisera identified the LPS antigen in only 36 strains. Prodigiosin production was restricted to serotypes O8, O6, and S3255 and strains with a rough or semirough LPS phenotype. Dot immunoassay appears to offer greater accuracy than agglutination tests for serotype identification in S. marcescens.